Water security in Basra Study economic reality and prospects for future water - حسن باسمة كزار (Journal of Economics and Administrative Sciences, 2015)
It can be said that the Security of water in Basra from the visual task vital strategic issues of concern to the attention of researchers in various attributions and those interested in water, environmental, economic, social, cultural and political affairs ... etc. This view of the great importance of the issue of water in the occupied Basra, which is characterized by parochialism and scarcity, When looking at the sources of our daily lives and in our reality today. We find that millions of people living on the two main exporters Tabaaan oil and water. And depleted oil wealth However Manfred him the most attention because we entered it surpasses all other sources of income, but is not it a little water, a source of permanent prosperity was still the lowest in the list of visual priority, We hope the local government in Basra to take care of the issue of water security, and putting it in the top position of priority, and that becomes the interest in this vital issue fateful tops the concerns of the province, and threads that Toady great interest and should be given priority in economic research and studies, especially after the decline of quotas assigned to Iraq as a result of the exploitation of neighboring countries to Iraq’s share of water. The search in Shan water security is to discuss the continuing existence and progress In the field of display research on the study of the economic reality of water resources in Basra and restrict research in the development and the possibility of securing the economic, political, legal and cultural aspects will be focused. Either in the field of water demand will mean the study determining the size and structure of demand and the prospect of change, as well as to rationalize water use and ensure that the development of Water Media culture appropriate, legal, economic, and administrative procedures